Adverse Cardiac Events Risks of Non-Obstructive Coronary Artery Disease by Cardiac CT Angiography at One-Year Follow-Up: Results of the Coronary Risk Determination in Intermediate Stratum Coronary CT Angiography (CORDISC) Study - Nwaedozie, Somto; Zhong, Chuyang; Umukoro, Peter; Yeung-Lai-Wah, Paul; Gabor, Rachel; Carmichael, Brett; Rolak, Stacey; Rokey, Roxann (International Journal of Innovative Research in Medical Science, 2022)
We conducted a retrospective cohort study of the adverse events at one year post-cardiac computed tomography (cardiac CT) using data gathered from the Marshfield Clinic Health System (MCHS) Cardiac CT registry to compare non-fatal myocardial infarction (MI), revascularization, all-cause mortality, and composite major adverse cardiac events (MACE) one year following cardiac CT in patients with non-obstructive coronary artery disease (CAD) and normal coronary arteries. From 2009 to 2017, the records of 2,649 patients who underwent cardiac CT were reviewed. CAD detected by cardiac CT was defined as normal (0% luminal stenosis) and non-obstructive (1-49% luminal stenosis). Clinical outcomes were nonfatal MI, revascularization, including percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG), all-cause mortality, and MACE. Cohorts were compared using t-tests and Fisher exact tests, and a logistic regression was performed to assess risk of clinical outcomes at one year. Compared with patients with normal coronary arteries, patients with non-obstructive coronary disease on cardiac CT had higher event rates of MACE (3.7% vs. 1.2%; P =0.006), revascularization (1.1% vs. 0.2%; P=0.033), and all-cause mortality (1.7% vs. 0.4%; P=0.012). After adjusting for baseline difference in demographics, risk factors, and medication use, the odds ratio of revascularization was 3.77 (95% CI: 1.03,13.79) and MACEs was 2.06 (95% CI: 0.94,4.51). Symptomatic congenital heart diseases accounted for about 50% of the non-death MACEs. Cardiac CT-defined non-obstructive CAD was associated with higher rates of revascularization, all-cause mortality and MACE compared to those with normal coronary arteries.